2019
DOI: 10.1186/s13741-019-0125-z
|View full text |Cite
|
Sign up to set email alerts
|

Large volume infusions of hydroxyethyl starch during cardiothoracic surgery may be associated with postoperative kidney injury: propensity-matched analysis

Abstract: BackgroundThe safety of intraoperative administration of hydroxyethyl starch (HES) has been debated. We hypothesized that intraoperative use of HES is associated with postoperative acute kidney injury (AKI) following cardiopulmonary bypass (CPB).Materials and methodsPatients who underwent cardiothoracic surgery using CPB between 2007 and 2014 were retrospectively reviewed. The incidence of AKI within 7 days after surgery, defined by the Kidney Disease Improving Global Outcome criteria, was compared for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Preoperative blood pressure was measured with the patient at rest in the ward the day before surgery with a Terumo electronic sphygmomanometer ES-H55 [ 15 ]. Intraoperative blood pressure data and patient demographic information were extracted from ORSYS using the Vipros data-mining software (DOWELL Co., Ltd., Japan) [ 16 ]. Intraoperative blood pressure values were measured with a Philips IntelliVue MP70.…”
Section: Methodsmentioning
confidence: 99%
“…Preoperative blood pressure was measured with the patient at rest in the ward the day before surgery with a Terumo electronic sphygmomanometer ES-H55 [ 15 ]. Intraoperative blood pressure data and patient demographic information were extracted from ORSYS using the Vipros data-mining software (DOWELL Co., Ltd., Japan) [ 16 ]. Intraoperative blood pressure values were measured with a Philips IntelliVue MP70.…”
Section: Methodsmentioning
confidence: 99%
“…Resuscitation with HES can lead to AKI, [ 36 ] which may be related to the decreased glomerular filtration and interstitial inflammatory changes caused by the high oncotic pressure of HES. [ 37 ] HES is also associated with deterioration of coagulation function, which can be partially explained by hemodilution. Other mechanisms can also explain this deterioration of coagulation, such as detrimental influences of factor VIII, factor XIII, fibrinolysis, and von Willebrand factor.…”
Section: Effects Of Different Resuscitation Fluids On the Glycocalyxmentioning
confidence: 99%
“…Importantly, the guidelines do not recommend using synthetic colloids first for fluid resuscitation, especially HES, [6] possibly because synthetic colloids have several disadvantages. Resuscitation with HES can lead to AKI, [36] which may be related to the decreased glomerular filtration and interstitial inflammatory changes caused by the high oncotic pressure of HES [37] . HES is also associated with deterioration of coagulation function, which can be partially explained by hemodilution.…”
Section: Effects Of Different Resuscitation Fluids On the Glycocalyxmentioning
confidence: 99%
“…When necessary, intravenous fluid administration should be performed using balanced crystalloid solutions [25,26]. Hydroxyethyl starch should not be used in cardiac surgery patients, because large randomized controlled trials (RCTs) demonstrated an increased risk for postoperative AKI and requirement for renal replacement therapy associated with the use of hydroxyethyl starch (HES) [27–29].…”
Section: Introductionmentioning
confidence: 99%